Reentry, desistance, and the responsibility of the state : let them back in - McGuinn, Stephen C., 1979- (Bingley, U.K. : Emerald Publishing Limited, 2018)
This work asks readers to reconsider punishment contracts in the United States. It illustrates the importance of state accountability and responsibility to those who are punished, while also focusing on the dual importance of desistance and re-entry. Looking across current criminological desistance literature, Stephen C. McGuinn shows the value of empowerment, meaning and, most of all, assimilation. Woven throughout the text, the work also captures the actual experiences of a man returning to society after eleven years in prison. He details his experiences in a daily journal, providing an honest and forthright account of the confusion and struggle of those who come home after lengthy prison stays. Through this account, readers are reminded of the importance of human connection and compassion. As researchers, as scientists, we must provide a map, or a language and narrative, on how to consider punishment in the US. In developing a new way to consider the process of desistance, this book champions the humanity in forgiveness and the compassion of justice.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Imprisonment -- United States; Prisoners -- Deinstitutionalization -- United States; Criminals -- Rehabilitation -- United States; Social Science -- Criminology; Crime & criminology